2014
DOI: 10.1074/jbc.m114.587873
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Protein Phosphatase 2A (PP2A) Prevents Mcl-1 Protein Dephosphorylation at the Thr-163/Ser-159 Phosphodegron, Dramatically Reducing Expression in Mcl-1-amplified Lymphoma Cells

Abstract: Background: Although Mcl-1 is normally subject to rapid turnover via a phosphodegron at Thr-163/Ser-159 and other pathways, sustained expression promotes viability/chemoresistance in cancer cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 70 publications
0
17
0
Order By: Relevance
“…64 Because stability of MCL1 is also regulated by phosphorylation, 65 it is tempting to speculate that such a mechanism may also operate to regulate MCL1 expression. Notably, however, inhibition of PP2A has been recently shown to enhance MCL1 degradation in lymphoma cells, 66 suggesting the situation may be more complex.…”
Section: Org Frommentioning
confidence: 99%
“…64 Because stability of MCL1 is also regulated by phosphorylation, 65 it is tempting to speculate that such a mechanism may also operate to regulate MCL1 expression. Notably, however, inhibition of PP2A has been recently shown to enhance MCL1 degradation in lymphoma cells, 66 suggesting the situation may be more complex.…”
Section: Org Frommentioning
confidence: 99%
“…The stability of MCL1 is mainly controlled by its phosphorylation status. 38,39 Phosphorylated MCL1 can be an easy target of an E3 ubiquitin ligase complex and is mostly driven to proteasomal degradation. 38,39 PP2A dephosphorylates MCL1 and prevents interaction between MCL1 and the complex.…”
Section: Discussionmentioning
confidence: 99%
“…38,39 Phosphorylated MCL1 can be an easy target of an E3 ubiquitin ligase complex and is mostly driven to proteasomal degradation. 38,39 PP2A dephosphorylates MCL1 and prevents interaction between MCL1 and the complex. 38,39 A previous study showed that PP2A inhibition dramatically decreased the protein levels of MCL1 within 2 h in Burkitt lymphoma cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, mass spectrometry analysis of IL-2R␤ revealed that Thr-450 is phosphorylated following CA treatment (data not shown). Interestingly, ERK1/2 can become activated by CA-induced inhibition of PP1 and PP2A (39). To delineate the kinetics of PP1 and PP2A inhibition on Thr-450 phosphorylation, YT cells were treated with 100 nM CA for 0 -60 min.…”
Section: Pp1 But Not Pp2a Negatively Regulates Phosphorylation Of Il-mentioning
confidence: 99%